The Cultural Semantics: Internalization of Javanese Language Local Wisdom to Prevent Moral Degradation Among Students - Siregar, Riadi Syafutra; Astutik, Dwi; Liestyasari, Siany Indria; Ghufronuddin; Parahita, Bagas Narendra (Universitas Muhammadiyah Malang, 2023)
This research is intended to describe the cultural semantics of the Javanese language's local wisdom and to internalize it to prevent moral degradation among students. This research uses the qualitative method with an ethnographic method approach. Data include phrases, sentences, and paragraphs containing information on the meaning, value, and function of local wisdom. Techniques of collecting data used were observation, recording, and in-depth interviews with 7 traditional figures of Javanese native speakers aged 45-60 years, 3 teachers of art and culture subject in Senior High School (SMA), and 5 Senior High School students domiciled in Surakarta. Semantic analysis was used to analyze the data. Data were transcribed, identified, and categorized using semantic relation analysis to be elaborated, then, based on its meaning, value, and context. The result shows that cultural semantics of the Javanese language local wisdom containing behavioral character value is classified into: (1) tepa selira (tolerance), (2) grapyak semanak (hospitality), (3) ewuh pakewuh (mutual respect), (4) pangerten (mutual understanding), (5) wawas dhiri (self-introspection), (6) andhap ashor (virtue), (7) lembah manah (humility) and (8) guyup rukun (concord). Semantics and its context are codes of conduct constituting ancestral heritage that can prevent moral degradation, control behavior, and shape character, particularly among students. This research offers two forms of implementation in education: (1) actualization in a school environment with extracurricular, co-curricular, and intracurricular activities, and (2) integration it into the learning.